Promo Code Strategy in E-Commerce: A Literature Review on its Impact on Customer Churn Rate and Managerial Implications - Adam, Moh. Nasrul Arief Setiawan; Podungge, Robiyati (AIBPM Publisher, 2025)
Promo codes are a prevalent digital marketing tactic employed in the e-commerce sector to enhance consumer acquisition and retention. Nevertheless, many research have cast skepticism on the enduring efficacy of promotional coupons, especially regarding their impact on diminishing customer turnover rates. This article offers a systematic literature review (SLR) derived from 123 scholarly papers spanning 2015 to 2024. The findings indicate that whereas promotional codes can enhance immediate customer acquisition, they negatively impact consumer loyalty when implemented without segmentation and loyalty measures. This analysis underscores the significance of a data-driven methodology and the integration of promotional codes with CRM systems to mitigate elevated attrition rates. This study employs various machine learning techniques, including Naive Bayes, Decision Trees, and k-NN. Consequently, k-NN with k=1 and Naïve Bayes produced the study's most favorable outcomes.